Comparison of Consumer Price Change In Traditional Pagesangan Market : June and July 2024 - Choirunnisa, Fajarani; Robbaniyyah, Nuzla Af'idatur (JSN : Jurnal Sains Natural, 2025)
This study aims to investigate the process of consumer price enumeration at the traditional Pagesangan Market, Mataram City, during July 2024, and analyze the percentage changes in commodity prices between June and July 2024. The research employs a descriptive qualitative approach, involving systematic steps such as field observations, formation of an enumeration team, training on survey methods, and direct data collection using questionnaires. Results indicate significant price fluctuations among key commodities: mackerel and cayenne pepper recorded price increases of up to 35% and 30%, respectively, due to limited supply and disrupted harvests. In contrast, tomato prices fell sharply by about 40% due to a surplus during the peak harvest season. Analysis reveals that seasonal factors, supply chain dynamics, and consumer demand are the primary drivers of these changes. The findings highlight the importance of maintaining price stability through targeted policies, particularly for essential goods that directly affect consumer purchasing power.